2011
DOI: 10.1021/om200695j
|View full text |Cite
|
Sign up to set email alerts
|

Bis(borylene) Complexes of Cobalt, Rhodium, and Iridium [(η5-C5H5)M(BNX2)2] (X = Me, SiH3, SiMe3): A Bonding Analysis

Abstract: Geometry, electronic structure, and bonding analysis of the terminal neutral bis­(borylene) complexes of cobalt, rhodium, and iridium [(η5-C5H5)­M­(BNX2)2] (M = Co, Rh, Ir; X = Me, SiH3, SiMe3) were investigated at the DFT/BP86/TZ2P/ZORA level of theory. The calculated geometry of iridium complex [(η5-C5H5)­Ir­{BN­(SiMe3)2}2] is in excellent agreement with structurally characterized iridium complex [(η5-C5Me5)­Ir­{BN­(SiMe3)2}2]. Pauling, Mayer, and Nalewajski-Mrozek bond multiplicities of the optimized struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 60 publications
(70 reference statements)
1
9
0
4
Order By: Relevance
“…[28] Borylene transfer from [(OC) 5 [29] DFT calculations by Pandey later showed that the degree of BÀBb onding in Group 9 cisbis(aminoborylenes) increases from Ir to Co, [30] yet without ever reaching the degree observed in 4.U nder photolytic conditions,the iron bis(borylene) complex 4,first underwent dimerization to diiron species 5 by loss of one CO ligand. Themost notable example remains the iron-templated catenation of four boron atoms presented in Scheme 3b.…”
Section: Introductionmentioning
confidence: 99%
“…[28] Borylene transfer from [(OC) 5 [29] DFT calculations by Pandey later showed that the degree of BÀBb onding in Group 9 cisbis(aminoborylenes) increases from Ir to Co, [30] yet without ever reaching the degree observed in 4.U nder photolytic conditions,the iron bis(borylene) complex 4,first underwent dimerization to diiron species 5 by loss of one CO ligand. Themost notable example remains the iron-templated catenation of four boron atoms presented in Scheme 3b.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of [Cp*Ir(NSiMe 3 ) 2 ] ( 1 d ) (Cp*=1,2,3,4,5‐pentamethylcyclopentadiene) is very different from 1 a where the diffuse metal orbitals of Ir push two borylene units far apart, 2.353 Å . A detailed bonding analysis of 1 d has been reported previously . The electronic structure of 1 d is shown in Figure e.…”
Section: Resultsmentioning
confidence: 75%
“…[3a] Ad etailed bonding analysis of 1d has been reported previously. [14] The electronic structure of 1d is shown in Figure 1e.…”
Section: Resultsmentioning
confidence: 99%
“…[20] Der Tabelle 1). [22] Wir gingen jedoch davon aus, dass die starke p-Donierung der Bor-gebundenen Aminogruppen das grçßte Hindernis für eine B-B-Kupplung darstellt und somit der Einsatz von Borylenliganden ohne p-basische Substituenten grçßeren Erfolg versprechen sollte.…”
Section: B-b-einfachbindungen üBer Borylenkupplungunclassified